2009
DOI: 10.1007/s10661-009-0979-5
|View full text |Cite
|
Sign up to set email alerts
|

Residue analysis of acephate and its metabolite methamidophos in open field and greenhouse pakchoi (Brassica campestris L.) by gas chromatography–tandem mass spectrometry

Abstract: The final residue analysis demonstrated that >50% of total methamidophos were resulted from the degradation of acephate 7 and 18 days after it was applied on the greenhouse pakchoi, respectively. While in the open-field pakchoi, >90% of total methamidophos was found to be the metabolite of acephate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Immense toxicity of acephate and methamidophos has been observed in environment including birds (Zinkl et al, 1981;Vyas et al, 1996), animals (Singh and Drewes, 1987), fishes (Szeto et al, 1979), soils and its microorganisms (Wu et al, 2010;Lo, 2010;Battu et al, 2009). Studies have revealed that acephate and methamidophos can persist on soils (Zhang et al, 2005;Battu et al, 2009), fruits and vegetables (Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010;Zhang et al, 2008), in dietary products (WHO, 2003(WHO, , 2005Nougade`re et al, 2012), cereal and other cash crops (Hiemstra & Kok, 2007;Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010). Both, acephate and methamidophos having high leaching capacity, contaminate agriculture soils by leaching behavior (Chai et al, 2009(Chai et al, , 2010.…”
Section: Mode Of Action and Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Immense toxicity of acephate and methamidophos has been observed in environment including birds (Zinkl et al, 1981;Vyas et al, 1996), animals (Singh and Drewes, 1987), fishes (Szeto et al, 1979), soils and its microorganisms (Wu et al, 2010;Lo, 2010;Battu et al, 2009). Studies have revealed that acephate and methamidophos can persist on soils (Zhang et al, 2005;Battu et al, 2009), fruits and vegetables (Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010;Zhang et al, 2008), in dietary products (WHO, 2003(WHO, , 2005Nougade`re et al, 2012), cereal and other cash crops (Hiemstra & Kok, 2007;Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010). Both, acephate and methamidophos having high leaching capacity, contaminate agriculture soils by leaching behavior (Chai et al, 2009(Chai et al, , 2010.…”
Section: Mode Of Action and Toxicitymentioning
confidence: 99%
“…In soil, plants and insects approximate half-life period of acephate is 3-6 days, although in some soils the half-life may be increased to more than 13-60 days due to variation of properties (physical, chemical and biological) of soils (Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010;Yen et al, 2000). Acidic nature of soil is responsible for long life spam of acephate in soils ( (Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Acephate is less persistent in the environment than many other organophosphates, with a half-life that ranges from 10 to 15 days at the recommended use rate, depending on the soil properties and environmental conditions. [6][7][8] However, the extensive and indiscriminate use of acephate has led to the accumulation of its residues in various agricultural products. Katz and Winter detected acephate residues in US domestic and imported fruit and vegetable samples and further found that domestic exposure to acephate was significantly higher.…”
Section: Introductionmentioning
confidence: 99%
“…The unregulated and indiscriminate application of insecticides has lead to their frequent appearance in water resources. Acephate and imidacloprid (Table 1) are low poisonous insecticides and are highly soluble in water (Chuanjiang et al 2010;Jemec et al 2007). These insecticides have raised much concern because of their intermediates, which are more toxic than their parent compounds (Anhalt et al 2007; Mohapatra et al 2011).…”
Section: Introductionmentioning
confidence: 99%